2019
DOI: 10.1016/j.geoderma.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of hydraulic conductivity and solute transport parameters and their spatial correlations to soil properties

Abstract: +55)16 35739501 Highlights• We study reactive and non-reactive solute transport in a tropical soil.• Solute transport parameters and hydraulic conductivity display high variability.• Solute transport parameters and soil properties present spatial dependence.• Spatial correlation is important up to 2.5 m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 86 publications
(113 reference statements)
1
23
0
Order By: Relevance
“…This contrast shows the great variability of this soil hydrology attribute, also demonstrated by the coefficient of variation (99.4%), being classified as having a high variability (CV > 35%) according to Wilding and Drees (1983). Godoy et al (2019) and She et al (2014) found a CV for K Sat of 122.0 and 50.8% in studies conducted in central-western Brazil and in the Loess Plateau region (China), respectively. Even when the data sets were transformed to logarithmic (ln), She et al (2017) obtained a CV above 35%.…”
Section: Exploratory Analysesmentioning
confidence: 96%
See 2 more Smart Citations
“…This contrast shows the great variability of this soil hydrology attribute, also demonstrated by the coefficient of variation (99.4%), being classified as having a high variability (CV > 35%) according to Wilding and Drees (1983). Godoy et al (2019) and She et al (2014) found a CV for K Sat of 122.0 and 50.8% in studies conducted in central-western Brazil and in the Loess Plateau region (China), respectively. Even when the data sets were transformed to logarithmic (ln), She et al (2017) obtained a CV above 35%.…”
Section: Exploratory Analysesmentioning
confidence: 96%
“…A negative correlation was observed between K Sat and Micro (− 0.51). According to Godoy et al (2019), this would be an inconsistent pattern considering that the K Sat of the soil has no physical relationship with soil micropores. This result indicates that a simple linear correlation matrix is not enough to explain the correlations between K Sat and other attributes, and thus, multivariate statistical tools should be considered for the assortment of spatial covariates and then a more efficient cokriging process.…”
Section: Cluster Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-soil chemical interactions change the hydro-mechanical behavior of soil by transferring components between water and soil, mainly via dissolution and precipitation, exchange and adsorption, and redox reactions [20][21][22]38,39]. In particular, the influence of these actions on soil permeability are significant [14,15,40,41].…”
Section: Response Of Permeability To Water-soil Chemical Interactionmentioning
confidence: 99%
“…These effects promote the transfer of components between soil and fluid, thus leading to changes of the surface morphology of particles and strengthening the soil structure [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%